El Enfoque de los Derechos Humanos y el Aporte de la Ley de Consulta Previa en la Participación Normativa y Administrativa de los Ciudadanos/Pueblos Indígenas en la Gestión de los Recursos Naturales - Soria Dall’Orso, Carlos Antonio Martín (2014)
The article begins by asking «How to overcome environmental conflicts?» To answer this question the article presents a characterization of the elements involved in environmental conflicts in the extractive industries. The article reviews our conception of law and the contribution of the human rights approach. With this foundation, the article presents the development of legislative and institutional framework governing environmental and social aspects in Peru.The article proposes alternatives for positive socio-environmental conflict’s transformationin the view of the approach of human rights. This can be achieved by promoting principles of environmental law and environmental management tools, also regulating negative impactsover social and cultural issues, promoting environmental justice, respecting indigenous peoples and citizen participation in granting administrative rights over natural resources.Finally, the article recounts the contribution of the Law on Prior Consultation to Indigenous Peoples and its impact on the participation of these communities in law and administrative processes related to the management of natural resources.